Dilema Penegakan Hukum Pidana Terhadap Prajurit TNI - Yudi Krismen (Jurnal Selat, 2014)
Many have a general criminal cases committed by members of the military of this country, but in law enforcement as if the members of the military as a criminal not touched by the criminal law, as a general jurisdiction to try criminal offenses committed by members of the TNI still under military justice. Moreover, the military justice system that are covered so much of the sense of justice. It should be criminal offenses committed by members of the military brought to the general court as mandated by the Constitution amendments 45 and MPR Decree No. VII / 2000, which regulates the separation of the role of the National Police Force constituted by the issuance of MPR NO.VI AND VII OF 2000 in Article 3, paragraph 4 of MPR Decree NO . VII / MPR / 2000, reads as follows: a) the Indonesian National Armed Forces are subject to the authority of the military court in the case of violations of military law and subject to the general judicial power in violation of the general criminal law, b) When the authority of the general court referred to in subsection ( 4a ) this article does not work then the soldiers subordinate judicial power which is regulated by law. This means that throughout the criminal law for military materiel ( KUHPM ) has not changed, it is difficult to apply an idea or a "political decision" contained in MPR Decree No. VII / 2000 , that the "soldiers are subject to the authority of the general court in the case of violation of the general criminal law". So keep referring to Law No. 31/1997 about the existing military justice governing the criminal justice common for soldiers, so that a wishful thinking will achieve "the principle of equality before the law" against members of the military and members of the military will continue to be the golden boy in this Republic. Keywords : Members of the military, military justice, public justice, the principle Aquality before the law